2006
DOI: 10.1177/107769900608300202
|View full text |Cite
|
Sign up to set email alerts
|

The Gendered Blogosphere: Examining Inequality using Network and Feminist Theory

Abstract: This study examined gender inequity among the most-read political blogs on the Web. Sampling over one year from blog rankings, we found that 10% of the top bloggers were women. Discourse analysis of bloggers' explanations for gender disparity revealed three dominant beliefs: women do not blog about politics, women's blogs lack quality, and top bloggers do not link to women's sites. We use network and feminist theory to explore these claims and offer suggestions for increasing the representation of female voice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 0 publications
1
45
2
Order By: Relevance
“…These results were not surprising given that a gender gap in general Internet users existed until the late 1990s in the US. Research since then, however, continues to identify a gender gap in political talk online (Stromer-Galley, 2002c;Stromer-Galley, 2002a;Harp & Tremayne, 2006;Trammell & Keshelashvili, 2005). 1 A gap also exists in European countries, including Germany (Albrecht, 2006), the Netherlands (Hagemann, 2002;Jankowski & van Selm, 2000), and Denmark (Jensen, 2003a).…”
Section: Who Talksmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were not surprising given that a gender gap in general Internet users existed until the late 1990s in the US. Research since then, however, continues to identify a gender gap in political talk online (Stromer-Galley, 2002c;Stromer-Galley, 2002a;Harp & Tremayne, 2006;Trammell & Keshelashvili, 2005). 1 A gap also exists in European countries, including Germany (Albrecht, 2006), the Netherlands (Hagemann, 2002;Jankowski & van Selm, 2000), and Denmark (Jensen, 2003a).…”
Section: Who Talksmentioning
confidence: 99%
“…Only one study has systematically investigated why women are not co-equal participants in the online discussion arena of blogs. Harp and Tremayne (2006) found that women were less likely to be top political bloggers in the US, in part because male bloggers do not link or draw attention to female political bloggers, unless they are also engaging in sexualized talk. These two studies suggest a "boy's club" exists online making it difficult for women to join in the conversation; When they do, they are belittled, attacked, and sexualized.…”
Section: Who Talksmentioning
confidence: 99%
“…Despite the promising power of digital technologies in education, questions related to literacy, misinterpretation, propagandizing, and integrity remain critical (Brooks, 2003;Harp & Tremayne, 2006;McPherson, 2006). Thus, RBL emerges as an alternative to close the gap between the power of digital technologies and these questions.…”
Section: Case Of Resource Based Learning In Educationmentioning
confidence: 99%
“…More recently, Coleman & Yochim (2008) have explored the 'symbolic annihilation of race'. The symbolic annihilation of Black women in the mainstream media as a consequence of intersectional invisibility is not necessarily remedied in the blogosphere as gender inequalities in the blogosphere do exist (Chen, 2011;Gregg, 2006;Harp & Tremayne 2006;Herring et al 2004;Pedersen, 2008). However, by utilising blogs as a strategy for voicing, Black women are able to experience discursive power on the internet.…”
Section: Voice and Visibilitymentioning
confidence: 99%